Disability health in medical education: development, implementation, and evaluation of a pilot curriculum at Stanford School of Medicine - Sapp, Richard W.; Lee, Edmund; Bereknyei Merrell, Sylvia; Schillinger, Erika; Lau, James N.; Feldman, Heidi M.; Poffenberger, Cori McClure (Frontiers in Medicine, 2024)
Background People with disabilities face significant healthcare disparities due to barriers to accessing care, negative attitudes of providers, and lack of education on disabilities for healthcare professionals. Physicians report discomfort when interacting with patients with disabilities, adding to the disparity, warranting research on medical school education. Objective Two educational interventions were structured: (1) a brief 2-h intervention in the mandatory curriculum and (2) a 9-week elective course which included interactions with individuals with disabilities through workshops and partner programs. We predicted that both of these interventions would result in improvements in attitude and empathy toward individuals with disabilities and reduce student anxiety. Methods During the 2018–2019 academic year, 54 students completed the surveys for the 2-h intervention and 8 students completed the 2-h intervention and elective course. Pre-, post-, and delayed post-intervention surveys (3 months after post survey) measured students’ attitudes, using validated surveys on attitudes, empathy and anxiety toward individuals with disabilities. Results Both educational interventions resulted in improved attitudes toward individuals with disabilities. However, students reported only feeling prepared to care for patients with disabilities after the elective course. The elective course, but not the 2-h course, significantly decreased student anxiety levels, likely due to more individual time working with individuals with disabilities. Delayed analysis after 3 months showed that both interventions had a lasting impact on attitudes and behavior change when caring for individuals with disabilities. Conclusion Medical education is effective at improving medical students’ attitudes and behaviors toward individuals with disabilities. A 2-h session can lead to a modest improvement in attitudes. However, more dedicated time and exposure to persons with disabilities results in a greater improvement in students’ attitudes, anxiety and preparedness.